2023
DOI: 10.3390/ani13142248
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Response in Digestive Gland of Mytilus coruscus under Heat Stress Using TMT-Based Proteomics

Abstract: Ocean warming can cause injury and death in mussels and is believed to be one of the main reasons for extensive die-offs of mussel populations worldwide. However, the biological processes by which mussels respond to heat stress are still unclear. In this study, we conducted an analysis of enzyme activity and TMT-labelled based proteomic in the digestive gland tissue of Mytilus coruscus after exposure to high temperatures. Our results showed that the activities of superoxide dismutase, acid phosphatase, lactate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…It has been reported that the MAPK/ERK pathway is involved in the heat stress response of marine invertebrates. 52 , 53 , 54 , 55 , 56 This pathway induces the expression of heat shock proteins, 57 , 58 alleviates oxidative stress and mitochondrial damage, 59 , 60 and ultimately promotes cell survival and inhibits apoptosis. 61 The results of site mutations of Cg ERK1/2 and co-transfection with Cg MAP2K1/2 proved that Cg MAP2K1/2 can enhance PK enzyme activity by increasing the phosphorylation levels of T187 and Y189 in Cg ERK1/2.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the MAPK/ERK pathway is involved in the heat stress response of marine invertebrates. 52 , 53 , 54 , 55 , 56 This pathway induces the expression of heat shock proteins, 57 , 58 alleviates oxidative stress and mitochondrial damage, 59 , 60 and ultimately promotes cell survival and inhibits apoptosis. 61 The results of site mutations of Cg ERK1/2 and co-transfection with Cg MAP2K1/2 proved that Cg MAP2K1/2 can enhance PK enzyme activity by increasing the phosphorylation levels of T187 and Y189 in Cg ERK1/2.…”
Section: Discussionmentioning
confidence: 99%